Geographical Distribution of Stunting Cases in Tanah Datar Regency - Dhea Sonya; Paus Iskarni (CV. CENDIKIA JENIUS INDONESIA, 2025)
Stunting remains a major public health challenge in Indonesia, including in Tanah Datar Regency, due to its long-term impacts on physical growth, cognitive development, and human resource quality. This study is necessary to understand how geographical factors contribute to variations in stunting prevalence across subdistricts. The objective of this research is to describe the geographical distribution of stunting cases and examine the relationship between geographical characteristics and prevalence differences. A mixed-methods approach was employed through spatial analysis using Geographic Information Systems (GIS) and interviews with related institutions. The sample included all 14 subdistricts (total sampling), while primary data were obtained from the PMDPPKB Office and the Health Office. Secondary data—including stunting prevalence, topography, road accessibility, distance to health facilities, and sanitation—were analyzed descriptively and spatially. The study was conducted in 2023, using triangulation techniques to ensure data validity. The results indicate an uneven distribution of stunting, with the highest prevalence found in Sungai Tarab (20.95%), Pariangan (19.08%), and Lima Kaum (18.64%). Influential geographical factors include hilly topography, limited road access, long distances to health services, inadequate clean water, and population distribution. In conclusion, geographical factors play a significant role in stunting disparities, indicating that interventions should be tailored to local spatial characteristics. It is recommended that the government strengthen basic infrastructure, mobile health services, and area-based mapping to ensure more targeted and sustainable nutrition interventions.